Fundamentals of jet propulsion with power generation applications - Flack, Ronald D. 1947- (Cambridge aerospace series, 2023)
The revised second edition of this introductory text focuses on the basic principles of jet engines and gas turbines. With rewritten chapters on operating characteristics of components and ideal and non-ideal cycle analysis, additional SI units in numerous examples, new and expanded end-of-chapter problems, and updated accompanying software.